Visual Culture and Arctic Voyages Personal and Public Art and Literature of the Franklin Search Expeditions - O'Dochartaigh, Eavan (Humanities, 2022)
Uncovering a wealth of neglected archival information, this book examines both visual and textual material from the mid-nineteenth century Franklin Search Expeditions to the Arctic, painstakingly tracing their influence on popular imagination. Its surprising findings present a compelling challenge to the still-dominant 'man-versus-nature' trope.